2021
DOI: 10.5888/pcd18.200550
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Social Media Use and Vaping Among Florida Adolescents, 2019

Abstract: What is already known on this topic?With the growing popularity of vaping and the proliferation of e-cigarette advertisements on social media, evidence has emerged about the association between social media exposure and vaping. What is added by this report?This study highlights the potentially stronger influence of Snapchat (daily and nondaily), Instagram (daily use), Facebook (nondaily use), and Twitter (nondaily use), on experimental and current vaping among adolescents in Florida.What are the implications f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 28 publications
1
16
0
2
Order By: Relevance
“…We, however, did not see an association between vaping status and ad recall. Findings, in combination with previous literature ( Lee et al, 2021 ) point to associations between social media use, e-cigarette prevention ad recall, and vaping status that warrant further exploration.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…We, however, did not see an association between vaping status and ad recall. Findings, in combination with previous literature ( Lee et al, 2021 ) point to associations between social media use, e-cigarette prevention ad recall, and vaping status that warrant further exploration.…”
Section: Discussionsupporting
confidence: 65%
“…However, social media use among youth is similar across a variety of demographic groups, with 95% having a smartphone and up to 85% using social media platforms ( Anderson and Jiang, 2018 ). Furthermore, youth who use social media are more likely to be experimenters or current vapers ( Lee et al, 2021 ), seemingly making them part of the FDA’s target population for the campaign. We, however, did not see an association between vaping status and ad recall.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-e-cigarette content on social media has the potential to shape positive social norms surrounding use among youth. Indeed, experimental and observational studies showed that youth who use social media frequently are more willing to try, have positive attitudes towards, have less harm perceptions to and are more likely to initiate e-cigarettes 7–9. Thus, surveillance of e-cigarettes on social media is critical to inform tobacco control efforts.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible Instagram plays a similar role among youths from other regions of the USAPI. Although further research is needed to confirm this, it appears that youths in USAPI reflect the patterns of exposure to tobacco products on social media that are observed on different regions of the US ( Lee et al, 2021 , Pokhrel et al, 2021 ). We did find youths in the current sample to be more exposed to tobacco content on Instagram than betel nut content.…”
Section: Discussionmentioning
confidence: 97%